2018
DOI: 10.1136/gutjnl-2017-315541
|View full text |Cite
|
Sign up to set email alerts
|

ARID1A, a SWI/SNF subunit, is critical to acinar cell homeostasis and regeneration and is a barrier to transformation and epithelial-mesenchymal transition in the pancreas

Abstract: ARID1A plays a key role in pancreatic acinar homeostasis and response to injury. Furthermore, ARID1A restrains oncogenic KRAS-driven formation of premalignant proliferative IPMN. -deficient PDACs are poorly differentiated and have mesenchymal features conferring migratory/invasive and stem-like properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
73
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 60 publications
5
73
0
Order By: Relevance
“…This is comparable to conditional deletion of Arid1a leading to depletion of Lgr5-expressing mouse intestinal stem cells, disrupting intestinal homeostasis 46 . In mice with co-expression of mutant Kras G12D allele ("KAC"), the pancreas developed LG-IPMNs and LG-PanINs ubiquitously, with the former resembling gastric type IPMNs in patients, as has been previously reported 7,8 . In contrast to "KC" mice, however, there was no stepwise progression of the LG precursors to HG precursor lesions, has also been reported to be repressed by p53 and the loss of p53 synergistically enhancing the Myc-induced tumorigenesis 47 .…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…This is comparable to conditional deletion of Arid1a leading to depletion of Lgr5-expressing mouse intestinal stem cells, disrupting intestinal homeostasis 46 . In mice with co-expression of mutant Kras G12D allele ("KAC"), the pancreas developed LG-IPMNs and LG-PanINs ubiquitously, with the former resembling gastric type IPMNs in patients, as has been previously reported 7,8 . In contrast to "KC" mice, however, there was no stepwise progression of the LG precursors to HG precursor lesions, has also been reported to be repressed by p53 and the loss of p53 synergistically enhancing the Myc-induced tumorigenesis 47 .…”
Section: Discussionmentioning
confidence: 65%
“…In contrast to "KC" mice, however, there was no stepwise progression of the LG precursors to HG precursor lesions, has also been reported to be repressed by p53 and the loss of p53 synergistically enhancing the Myc-induced tumorigenesis 47 . The appearance of these highly ranked aberrant signaling nodes was not unexpected, since the prior studies in autochthonous models have also reported upregulation of EMT-associated genes 8 and MYC activation within the resulting Arid1a-null cancers 7 and low ARID1A expression significantly correlated with low Ki-67 labeling index and negative p53 expression in breast cancer patients 48 . One interesting facet that emerged from the GSEA was downregulation of Ras signaling in the "KAC" lines, which was confirmed by assessment of MAPK activity.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…In Gut , Wang et al aim at exploring the implications of the SWI/SNF family member Arid1a (AT-Rich Interaction Domain 1A) in pancreatic homeoestasis and PDAC pathogenesis 6. By combining phenotypic studies in genetically engineered mouse models with pancreas specific Arid1a depletion with functional and mechanistic analyses in primary PDAC cells derived from these mice the authors illustrate the role of Arid1a in maintaining acinar cell identity and characterise unhampered Arid1a expression and activity as a pivotal barrier for pancreatic transformation and PDAC progression.…”
mentioning
confidence: 99%